(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Pregnancy with Addison’s disease is very rare. Addison’s disease is caused by destruction or dysfunction of the adrenal cortices. A 25 years old lady with Addison’s disease receiving chronic treatment with prednisolone (5mg) 1+½+0 tab daily was admitted in 0bs & Gynae Department, BSMMU on 25th October,’09 with 2nd gravida , 38 wks of pregnancy. Caesarean section was done on 26th October, ’09. A male baby of 2.5 kg was delivered. Her peroperative and postoperative periods were uneventful. Inj. Hydrocortisone was given peroperatively and postoperatively. Patient was discharged on 7th P.O.D. with above dose of Tab prednisolone. DOI: http://dx.doi.org/10.3329/jbcps.v29i3.9438 JBCPS 2011; 29(3): 163-165